Distinguishing Positional Uncertainty from True Mobility in Single-Molecule Trajectories That Exhibit Multiple Diffusive Modes - Kastantin, Mark (2012)
Although imperfect spatial localization in single-molecule object tracking experiments has long been recognized to induce apparent motion in an immobile population of molecules, this effect is often ignored or incorrectly analyzed for mobile molecules. In particular, apparent motion due to positional uncertainty is often incorrectly assigned as a distinct diffusive mode. Here we show that, due to both static and dynamic contributions, positional uncertainty does not introduce a new apparent diffusive mode into trajectories, but instead causes a systematic shift of each measured diffusion coefficient. This shift is relatively simple: a factor of σ(2)/Δt is added to each diffusion coefficient, where σ is the positional uncertainty length scale and Δt is the time interval between observations. Therefore, by calculating the apparent diffusion coefficients as a function of Δt, it is straightforward to separate the true diffusion coefficients from the effective positional uncertainty. As a concrete demonstration, we apply this approach to the diffusion of the protein fibrinogen adsorbed to a hydrophobic surface, a system that exhibits three distinct modes of diffusion.